Transitions in the Avant-garde: Dada to Surrealism as illustrated by Ramón Gómez de la Serna’s novel El Incongruente? (Groundings Undergraduate, 2010)
Written on the cusp between two movements, El Incongruente by Ramon Gómez de la Serna eloquently illustrates the transition between Dada and Surrealism. Utilising key Dadaist principles – such as the renunciation of logic, chance combinations of chapters and the juxtaposition of contradictory imagery – combined with Surrealist elements such as a focus on dreams and the passing of time, Gómez de la Serna constructs the puzzling world in which Gustavo lives. El Incongruente breaks with literary tradition eulogizing Dadaist elements whilst still representing the harbinger of Surrealism.
Keywords: El Incongruente; Ramon Gómez de la Serna; Dada; Surrealism; Dadaism; Transition; Tradition